Study of spun pile connection with steel jacket strengthening. Issue 1 (January 2021) - Orientilize, M; Prakoso, W A; Fadel, M; Fernaldy, R P
Abstract: The amount of spiral reinforcement in the spun pile manufactured in Indonesia is below the minimum requirement. Additional shear reinforcement is needed, particularly on a pile at the adjacent pile cap. To cope with the deficiency, steel jacket is initiated to strengthen the pile. A numerical study was performed to study the effect of steel jacket addition to spun pile behavior. Two different software, SAP and Abaqus were employed. Pushover analysis was performed with a monotonic loading approach. The parameters studied were the steel jacket's thickness and the existence of adhesive between the steel and the concrete surface. Brittle behavior was detected with the presence of steel jacket which was indicated by the force displacement curve. The steel improves the strength of the spun pile connection but decreases the ductility. It seems that pile is in over reinforced condition. To get a thorough understanding, a 3D model with Abaqus software was performed. Steel jacket is applied on the spun pile without rebar inside concrete fill and thinner steel was selected to prevent over reinforce. Hence, different results were found where spun pile connections behave in a ductile manner. Steel jacket improves not only the strength of spun pile connection but also the ductility.